Mob2 Insufficiency Disrupts Neuronal Migration in the Developing Cortex - O’Neill, Adam C.; Kyrousi, Christina; Einsiedler, Melanie; Burtscher, Ingo; Drukker, Micha; Markie, David M.; Kirk, Edwin P.; Götz, Magdalena; Robertson, Stephen P.; Cappello, Silvia (Frontiers in Cellular Neuroscience, 2018)
Disorders of neuronal mispositioning during brain development are phenotypically heterogeneous and their genetic causes remain largely unknown. Here, we report biallelic variants in a Hippo signalling factor - MOB2 - in a patient with one such disorder, periventricular nodular heterotopia (PH). Genetic and cellular analysis of both variants confirmed them to be loss-of-function with enhanced sensitivity to transcript degradation via nonsense mediated decay or increased protein turnover via the proteasome. Knockdown of Mob2 within the developing mouse cortex demonstrated its role in neuronal positioning. Cilial positioning and number within migrating neurons was also impaired with comparable defects detected following a reduction in levels of an upstream modulator of Mob2 function, Dchs1, a previously identified locus associated with PH. Moreover, reduced Mob2 expression increased phosphorylation of Filamin A, an actin cross-linking protein frequently mutated in cases of this disorder. These results reveal a key role for Mob2 in correct neuronal positioning within the developing cortex and outline a new candidate locus for PH development.